Case Report: Variable Pharmacokinetic Profile of Eculizumab in an aHUS Patient - Bouwmeester, Romy N.; Ter Avest, Mendy; Wijnsma, Kioa L.; Duineveld, Caroline; ter Heine, Rob; Volokhina, Elena B.; Van Den Heuvel, Lambertus P. W. J.; Wetzels, Jack F. M.; van de Kar, Nicole C. A. J. (Frontiers in Immunology, 2021)
BACKGROUND With the introduction of eculizumab, a C5-inhibitor, morbidity and mortality improved significantly for patients with atypical hemolytic uremic syndrome (aHUS). In view of the high costs, actual needs of the drug, and increasing evidence in literature, aHUS patients can be treated according to a restrictive eculizumab regimen. We retrospectively analysed the pharmacokinetic and dynamic parameters of eculizumab in one patient in time, emphasizing various factors which could be taken into account during tapering of treatment. CASE PRESENTATION A nowadays 18-year-old male with a severe, frequently relapsing form of atypical HUS due to a hybrid CFH/CFHR1 gene in combination with the homozygous factor H haplotype, required chronic plasma therapy (PT), including periods with plasma infusion, from the age of onset at 5 months until initiation of eculizumab at the age of 11 years. A mild but stable chronic kidney disease (CKD) and 9 years of disease remission enabled prolongation of eculizumab interval. At the age of 15 years, a sudden yet multifactorial progression of chronic kidney disease (CKD) was observed, without any signs of disease recurrence. However, an acquired glomerulocystic disease, a reduced left kidney function, and abnormal abdominal venous system of unknown etiology were found. In addition, after an aHUS relapse, an unexpected increase in intra-patient variability of eculizumab concentrations was seen. Retrospective pharmacokinetic analysis revealed a change in eculizumab clearance, associated with a simultaneous increase in proteinuria. CONCLUSION High intra-patient variability of eculizumab pharmacokinetics were observed over time, emphasizing the necessity for adequate and continuous therapeutic drug monitoring in aHUS patients. Eculizumab serum trough levels together with complement activation markers (CH50) should be frequently assessed, especially during tapering of drug therapy and / or changing clinical conditions in the patient. In addition, an increase in proteinuria could result in urinary eculizumab loss, indicating that urinary monitoring of eculizumab may be important in aHUS patients with an unexplained decline in serum concentrations.